WHAT DRIVES YOUNG WOMEN TO JOIN THE PAKISTAN ARMED FORCES? AN EXPLORATORY STUDY OF MOTIVATIONAL FACTORS - Mustafa, Nazia; Kiani, Shoaib (Pakistan Armed Forces Medical Journal, 2021)
Objective: To explore the motivational factors for women to join Pakistan army.Study Design: Exploratory study design.Place and Duration: The study was conducted at Army selection and Recruitment Centre on the female graduates from various universities of Islamabad/Rawalpindi who were coming for induction in army, from March 2018.Methodology: The study was conducted in two phases; in phase I, Semi-structured interviews of 10 lady officers were carried out to gauge the motivational factors to join Army. In phase II, data of 792 female graduates from various universities of Islamabad/Rawalpindi was collected through socio-demographic form and the checklist about motivational factors developed during phase I to join armed forces.Results: Results revealed that maximum individuals (22%) graded “Patriotism” as prime reason to join Army while a minor segment (1%) cited financial incentive as driving factor. Percentages of other factors, in order of precedence are; “Feeling Proud” (18%), “Strong Social Standing” (16%), “Quality of Life” (10%), Charm of Uniform (8%), Bright Career (6%), Job Security (5%), Family Lineage (5%), Adventurous Job (5%) and Marriage (4%). Further to this, there were differences in women’s motivation to join Army from various professions.Conclusion: Motivation for opting military career is a complex phenomenon of inter-related factors. Therefore, we should consider all these factors together to select highly motivated, skilled/qualified and loyal individuals.